Single-tube isothermal label-free fluorescent sensor for pathogen detection based on genetic signatures - Reed, Mark A.; Gerasimova, Yulia V. (Frontiers in Chemistry, 2022)
We report on a single-tube biosensor for real-time detection of bacterial pathogens with multiplex capabilities. The biosensor consists of two DNA probes, which bind to the complementary fragment of a bacterial rRNA to form a three-way junction (3WJ) nucleic acid structure. One of the probes encodes a light-up RNA aptamer under T7 promoter. It allows for generation of multiple aptamer copies due to elongation and transcription of the 3WJ structure in the presence of the cognate target. The aptamer coordinates and thereby enhances fluorescence of a cognate fluorogenic dye, allowing for fluorescent detection of the RNA target. Multiple aptamer copies can be produced from a single target-dependent 3WJ structure allowing for amplification and visual observation of the signal. The sensor is excellent in analyzing folded RNA targets and differentiating between closely related sequences due to the multicomponent character of the target-interrogating probe. Response to unamplified samples of total bacterial RNA from Mycobacterium tuberculosis complex or Escherichia coli was observed with excellent selectivity within 30 minutes under isothermal conditions at 50oC in a one-tube one-step assay. Several bacterial species can be detected in multiplex by utilizing biosensors with the template strands encoding different light-up aptamers. The isothermal one-tube-one-step format of the assay and the possibility to monitor the signal visually makes it amenable to use in a point-of-care scenario.